Effects of mind mapping-based instruction on student cognitive learning outcomes: a meta-analysis - Shi, Yinghui; Yang, Huiyun; Dou, Yi; Zeng, Yong (Asia Pacific education review, 2023)
Mind mapping is a visualization tool used in instruction that can be applied by learners to generate ideas, take notes, organize thinking, and develop concepts. Instruction using mind mapping is becoming increasingly commonly used in education. However, research has produced inconsistent results regarding the effectiveness of mind mapping-based instruction on student learning outcomes. Using the meta-analysis of 21 studies, this study investigates the overall effectiveness of the mind mapping-based instructions on students’ learning outcomes in comparison with that of traditional instruction. Mind mapping-based instruction has been found to have a more positive influence on students’ cognitive learning outcomes than traditional instruction. Analysis of moderator variables suggests that the subject matter and educational level are important factors in the effectiveness of mind mapping-based instruction. Lower-grade students are more susceptible to the influence of mind mapping-based instruction than higher-grade students, and mind mapping-based instruction helps students improve their cognitive learning outcomes in all subjects, especially in the Science, Technology, Engineering, and Math disciplines.